ANALISA STRATEGI PEMASARAN FOOD AND BEVERAGE DEPARTMENT DALAM MENINGKATKAN VOLUME PENJUALAN PADA LA BELLA VITA LOUNGE DI HOTEL BEST WESTERN PREMIER PANBIL BATAM - Wahyudi Ilham (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
This study aims to analyze the marketing strategies implemented by the Food and Beverage Department at La Bella Vita Lounge, Best Western Premier Panbil Hotel Batam, with the goal of increasing sales volume. The research employs a qualitative and quantitative approach to explore in-depth information about the applied marketing strategies and their impact on sales growth. The research methodology involves interviews with La Bella Vita Lounge management and the analysis of historical sales data for a specific period. SWOT analysis is utilized to evaluate the strengths, weaknesses, opportunities, and threats faced by the Food and Beverage Department. Additionally, questionnaires may be distributed to customers to gather their insights on service quality and consumer preferences. The study's findings are expected to provide a better understanding of the effectiveness of existing marketing strategies and offer recommendations for improvement or refinement to enhance the competitiveness of La Bella Vita Lounge in the Batam Food and Beverage market. The practical implications of this research are anticipated to assist the management of Best Western Premier Panbil Hotel Batam in optimizing their marketing strategies and achieving higher sales objectives.